Transition of Medical Waste Management (MWM) from Romania to the Circular Economy Paradigm: Expectations and Objective Limits - Patricia Bostan; Cristina Lazar; Ionel Bostan (Ovidius University Annals: Economic Sciences Series, 2023)
The circular economy and medical waste management (MWM) are important for protecting the environment and human health. In the healthcare sector, the circular economy can be applied by reusing medical equipment, recycling materials from medical waste and adopting more sustainable practices such as reducing energy consumption and using more environmentally friendly materials. Clearly, reusing medical equipment reduces the amount of medical waste and can reduce costs. The authors intend through this paper to address MWM in Romania within a more sustainable circular system, attempting to identify the pros and cons, as well as the limitations, of a massive shift of MWM to circular economy principles. The structure of this paper includes, following this introductory part (1): Theoretical background (2), Research methodology (3), Circular economy and the healthcare waste management system (4), Approaching healthcare waste management within a more sustainable circular system (5), Limits of the massive shift of MWM to circular economy principles (6) and Conclusions (7).